Private capital inflow and growth in former Soviet-bloc countries: Roles of stock market and demand-side macroeconomic policy - Adil H. Suliman; Mohammed Zakaullah Shariff; Humoud AlMutairi; Khaled ElMawazini (The European Journal of Comparative Economics (EJCE), 2019)
This paper contributes to the empirical literature by investigating the impact of private capital inflows on economic growth across former Soviet-bloc countries between 1990 and 2015. Roles of the stock market and of demand-side macroeconomic policy are investigated using panel data analysis. The result suggests that though foreign direct investment (FDI) contributing relatively more to economic growth than foreign portfolio investments (FPI), it interactswith stock market trading to negatively influence growth. Final Consumption Expenditure, Inflation, and Gross Savings have negative influences on growth. Our results support the notion that private capital inflow does not allowed to provide sufficient capital to local savings and growth, which is a sign of the crowding-out effect. We suggest that the demand-side macroeconomic policy and stock market activity should tailored more to support economic growth.
Keywords: C23; F21; F43; 330; private capital flow; demand-side macroeconomic policy; economic growth; panel data; generalized method of moments(GMM); former Soviet-bloc countries